Iatrogenesis in parenteral feeding - arcillo Vallejo, Antonio M; Marcillo Vallejo, Errol (Revista Universidad de Guayaquil, 1990)
It is necessary to establish, albeit briefly, the true meaning of the word iatrogenesis. It comes from two Greek words: YATROS which means DOCTOR, and GUENNAN, which means PRODUCE; that is, produced for the doctor or medicines. We would complement the concept as PROCEDURES OR ATTITUDES PRODUCED BY THE DOCTOR OR MEDICATIONS WITH HARMFUL REPERCUSSIONS FOR THE PATIENT.